Effect of Slope Chute Angle of HAP Magnetic Separator to the Acquisition of Nickel Matte from Undersized Product Resulted by Pierce Smith Converter Machine - Nurhayati Indah Ciptasari; Egidius Arya Parande; Johny Wahyuadi Soedarsono; Agus Budi Prasetyo; Wahyu Mayangsari; Reza Miftahul Ulum; Ahmad Maksum (Recent in Engineering Science and Technology, 2023)
The prototype of a magnetic separator was initiated and manufactured for handling undersized products of Pierce Smith Converter which has been channeled to a temporary shelter called a matte pond. It was dredged three to four times a year and it’s costly. This expenditure can be minimized by the manufacture of magnetic separators that are used to attract undersized nickel products. The manufacture of this prototype uses a scale of 1:20.000 for the volume of water and nickel matte, while for chute and magnetic drums with a scale of 1:4 from the conditions in the field. This research aims to determine whether magnetic separators are relevant for installation in the nickel processing industry, with the slope angle of the chute and magnetic power as the main parameters. Thus the matte pond can be minimized and undersized products can be directly processed and distributed to consumers. The material used in the manufacture of this prototype is aluminum sheet 1/16 which is rolled for magnetic drums, aluminum sheet 1/8 in for chute, copper wire 0.5 mm and mild steel, lathe for rods and axis, and bending for magnetic holders. The result of this magnetic separator prototype is 24.48% nickel can be attracted.